Advanced training in child psychology: Key elements in offering a Doctor of Psychology (DPsych) programme in South Africa. Issue 4 (31st August 2016) - van der Watt, Ronél; Sharp, Carla
Abstract : The aim of this article is to propose some benchmarks for a Doctor of Psychology (DPsych) in advanced training in Child Psychology in South Africa, and to highlight key elements in offering such a programme. In doing so, we use as case illustration an existing DPsych programme currently being offered at the University of the Free State, South Africa. We consider advanced child psychology training to registered psychologists in the clinical, counselling and educational categories. The DPsych option encompasses clinical practice, research, training, selection, and student outcomes in the context of theory as well as evidence-based practices. A wider adoption of a DPsych, focusing on child psychology, would add value to the integration of the best available research and clinical expertise in child mental health care in South Africa.